Remediating Learning Problems (Book Review). - deBruyn, Jean Hicks (Journal of Learning Disabilities, 1976)
Reviews the book 'Remediating Learning Problems: A Developmental Curriculum,' by Clara M. Chaney and Nancy R. Miles.